Correlates of Objectively Measured Physical Activity Among People With Multiple Sclerosis: A Cross-Sectional Study - Fortune, Jennifer; Norris, Meriel; Stennett, Andrea; Kilbride, Cherry; Lavelle, Grace; Hendrie, Wendy; DeSouza, Lorraine; Victor, Christina; Ryan, Jennifer Mary (Frontiers in Rehabilitation Sciences, 2021)
Abstract Background Identifying correlates of physical activity for people with multiple sclerosis (MS) is essential to design effective physical activity interventions. Methods: Participants completed a battery of questionnaires and wore an ActiGraph accelerometer. Light physical activity and moderate-to-vigorous physical activity (min/day) were calculated. Associations were examined using multiple linear regression adjusted for demographic and clinical confounders. Results: Fifty-eight adults with MS participated (mean±SD age: 56.8 ± 9.2yr; 67% female). MS type was associated with time in light physical activity. Participants with secondary progressive MS (B=-54.0, 95% CI -84.7 to -23.3) and primary progressive MS (B=-42.9, 95% CI -77.5 to -8.3) spent less time in light physical activity than those with relapsing remitting MS. Walking capacity (MSWS-12) was associated with time in moderate-to-vigorous physical activity (B=-0.36, 95% CI -0.72 to -0.01). Conclusion This study identifies walking capacity and type of MS as correlates of PA, which may inform development of interventions to promote physical activity.